Estrutura populacional e ecologia da nidificação do jacaré-açu Melanosuchus niger (spix, 1825) na reserva extrativista Lago do Cuniã – Rondônia, Brasil - Helena Gurjão Pinheiro do Val (2021)
Ecology and the dynamics of population aim to study how natural populations fluctuate throughout space-time scales, regarding indexes of birth, mortality and dispersion. These aspects alter the abundance of these populations in specific areas and time. They are important aspects to determine whether a specific population is growing, maintaining or declining. In order to enable a sustainable management of natural populations, it is necessary to obtain basic information about managed species, such as size, recruitment, structure and sex ratio of populations. In this dissertation, we study aspects regarding population structure, such as abundance, density, distribution, size structure and sex ratio of crocodilians at Extractive Reserve Lago do Cuniã (Lake Cuniã), State of Rondônia – Brazil. Aspects related to the fecundity of the breeding females, such as litter size, nesting ecology and sex ratio of offspring generated in 2019 were also studied. The methods included night counts, capture, biometrics and sexing of individuals as well as active search of nests and monitoring of a reproductive female. From the counts, a high abundance of crocodilians was estimated at about 19 thousand individuals, of two or more species in sympatry. The population contribution of young-adults differs between Caiman crocodilus and Melanosuchus niger, which may interfere in the population dynamics of the species.Despite being sympatric, there is segregation between C. crocodilus and M. niger due to different environmental preferences.The 2:1 M/F sex ratio for M. niger suggests a high reproductive potential for the population. Regarding reproduction, nineteen nests were found, distributed in three bodies of water at the Extractive Reserve.The expected sex ratio as a function of nest temperature corroborates that obtained for the sample of adults studied.Great variability was found for mass, width and length of the eggs. Unlike the finding for other species of crocodilians, no relationships were found between the biometric characteristics of the alligator litters, such as width, length, mass and number of eggs.The home range analysis of a breeding female resulted in an area of 101.6 ha, but it was not possible to conclude on the parental care of the nest.Such information is important to understand how the species relate to the environment in which they are inserted in order to support actions of sustainable management and conservation of species in the Lago do Cuniã (Lake Cuniã) Extractive Reserve.